Penerapan Model Pembelajaran Open Ended Untuk Meningkatkan Kemampuan Berpikir Kreatif dan Penalaran Matematis Siswa - Michelle Ivana Filbertha; Sahat Saragih (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
This research aims to find out how to improve the creative thinking and mathematical reasoning abilities of class after implementing learning based on the open ended learning model. This research is Classroom Action Research (PTK). Data was collected through tests of students' creative thinking and mathematical reasoning abilities at the end of each cycle and observation sheets of teacher and student activities. The results of the research show that: (1) The increase in students' creative thinking and mathematical reasoning abilities is classified as a medium improvement criterion with the respective average N-gain values being 0.53 and 0.49. And the percentage of classical completion of students' creative thinking abilities after implementing cycle I increased to 47.22% and after implementing cycle II actions increased to 86.11%. As well as the percentage of classical completeness of students' mathematical reasoning abilities after implementing cycle I actions increased to 47.22% and after implementing cycle II actions increased to 91.67%; (2) The process of students' answers in completing tests on students' creative thinking abilities and mathematical reasoning can be said to be good.